How do Pre-service English Teachers Implement Deep Learning Strategies within the TPACK Framework During their Teaching Practicum - karim, Muhammad Rusydan Al; Priajana, Nana; Hidayat, Hendi (EDUCAFL: Journal on Education of English as Foreign Language, 2026)
This study investigated the implementation of deep learning strategies within the Technological Pedagogical Content Knowledge (TPACK) framework during the teaching practicum of pre-service English teachers in Cirebon. The study aimed to explore how pre-service teachers integrated technology, pedagogy, and content knowledge to support meaningful English language learning. A qualitative case study design was employed involving six pre-service English teachers and two mentor teachers selected through purposive sampling. Data were collected through semi-structured interviews and questionnaires and analyzed using thematic analysis based on Braun and Clarke’s framework. The findings revealed four major themes: student-centered and interactive learning practices, technology integration to enhance learning, strategic instructional design, and deep learning-oriented pedagogical approaches. The participants implemented discussion, collaboration, open-ended questioning, and problem-solving activities to encourage active participation and critical thinking. Various digital platforms such as Google Classroom, YouTube, Canva, and Quizizz were also integrated to support interactive and meaningful learning. In addition, participants aligned learning objectives, pedagogical strategies, and technology before conducting instruction. Overall, the study indicates that the integration of deep learning and TPACK promotes meaningful, student-centered, and technology-enhanced English language learning during teaching practicum.